ALTERATION IN CARBOHYDRATE METABOLISM BY SUB-ACUTE LEAD EXPOSURE: A DOSE-DEPENDENT STUDY - Das, Pritha; Pal, Sudipta (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The study was conducted to evaluate the dose-dependent effects of sub-acute lead exposure on certain aspects of carbohydrate metabolism. Methods: Swiss albino male mice (weighing 30-35 g) were selected for the present study and divided into five groups; one control group and others lead-treated groups i.e. Group A (5 mg/kg body weight), Group B (10 mg/kg body weight), Group C (15 mg/kg body weight) and Group D (20 mg/kg body weight). Parameters like blood and liver glucose, glycogen and pyruvic acid contents were determined in liver tissue. The enzyme activities like pyruvate dehydrogenase, malate dehydrogenase and glucose 6-phosphatase were recorded in that tissue. Additionally, free amino acid nitrogen content and transaminase enzyme activities were also evaluated in liver tissue of mice. Results: The study reveals that lead caused a significant diminution of blood and hepatic glucose levels and fall in liver glycogen content in a dose-dependent manner, the highest effect was observed in animals treated with lead at a dose of 20 mg/kg body weight. Glucose 6-phosphatase activity was decreased significantly in all the treated groups. There was a dose-dependent increase in pyruvic acid content whereas pyruvate dehydrogenase, malate dehydrogenase and transaminase enzyme activities were significantly depressed in a dose-dependent fashion in all the treated animals. Additionally, lead treatment significantly (p<0.001) enhanced free amino acid nitrogen in the liver to provide a substrate for gluconeogenesis. Conclusion: It is suggested that an adaptive mechanism is initiated by stimulating and retarding glycogenolytic and glycolytic activity and also by rising in the content of free amino acid nitrogen to recover from the lead stressed toxic manifestation